Six Out of Ten Women with Recurrent Urinary Tract Infections Complain of Distressful Sexual Dysfunction – A Case-Control Study - Boeri, Luca (Sci Rep, 2017)
Uncomplicated recurrent urinary tract infections (rUTIs) are common among reproductive-aged women. We aimed to assess the prevalence and predictors of sexual dysfunction (FSD) in a cohort of women with rUTIs and compare their psychometric scores to those of matched controls. Data from 147 rUTIs women and 150 healthy controls were analysed. Participants completed the International Prostatic Symptoms Score (IPSS), the Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale (SDS). Descriptive statistics and logistic regression models tested prevalence and predictors of distressful FSD. Women with rUTIs had lower FSFI scores (p < 0.001) and a greater proportion of pathological FSFI (78.9% vs. 21.4%; p < 0.001) and SDS scores (77.8% vs. 21.4%; p < 0.001) than controls. Of rUTIs patients, 88 (60%), 77 (52.2%), and 75 (51.1%) reported pathological scores for FSFI-pain, lubrication and arousal, respectively; moreover, 64% had concomitant pathological FSFI and SDS scores. Age, IPSS severity, rUTIs, a history of ≥6 UTIs/year and a history of constipation were independent predictors of pathologic FSFI and SDS (all p ≤ 0.05). In conclusion, up to 80% of women with rUTIs showed pathologic FSFI and SDS scores, with 60% reporting scores suggestive of distressful FSD. Having ≥6 UTIs/year and a history of constipation independently predicted distressful FSD.